THE POTENTIAL OF THE EUROPEAN SMART SPECIALISATION PLATFORM FOR THE DIGITAL TRANSFORMATION OF UKRAINE’S ECONOMY - OLESHKO Аnna; CHUBYK, Andriy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article explores the key aspects of using the potential of the European Smart Specialisation Platform to formulate national and regional policies and strategies in the context of digital transformation. It analyses the potential of the Smart Specialisation Platform as an innovative tool for digital transformation to ensure smart specialisation, research, innovation and competitive advantage of regions. Research on smart specialisation as an integral element of digital transformation is based on new concepts of global development, such as sustainability, smartisation, green transition and digitalisation. The key drivers of the smart specialisation strategy are substantiated, in particular localisation, prioritisation and engagement. The main directions of smart specialisation are its adaptation to the specificities of regional needs, stimulating the diffusion of innovation, ensuring monitoring and evaluation in compliance with key performance indicators, strengthening international cooperation and reinforcing links with other EU programmes and priorities, ensuring good governance and promoting inclusive growth. The implementation of the Smart Specialisation Strategy in Ukraine involves joining EU initiatives and bringing together financial and non-financial enterprises, research institutions, higher and vocational education institutions and NGOs to modernise and create a new industrial and innovation structure based on digital transformation. It is concluded that intensifying the participation of Ukrainian enterprises, scientific institutions and the state in the implementation of smart specialisation ideas through cooperation with the EU will strengthen Ukraine’s research potential, ensure the digitalisation of citizens and enterprises and increase the competitiveness of the economy based on digital transformation. Innovative and smart economic transformation involves the formation of an effective business environment based on international cooperation and partnerships to achieve specific goals under the smart specialisation strategy.